A man without breath [large type] : a Bernie Gunther novel - Kerr, Philip (Kerr, Philip. Bernie Gunther novel., 2013)
March, 1943. A month after the stunning defeat at Stalingrad, morale is low, discipline is at risk. Now word reaches Berlin of a Red massacre of Polish officers near Smolensk. If true, the message to the troops is clear: Fight on or risk certain death. For once, the Wehrmacht and Goebbels agree: they want irrefutable evidence of this Russian atrocity, and the investigation must be overseen by a professional. And so Bernie Gunther is dispatched to Smolensk. (Bestseller)